RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN GURU BERBASIS WEB (STUDI KASUS MI NU 43 WONOREJO KENDAL) (Information Technology and Telematics, 2015)
Abstract Teacher is one of the main factors in determining the quality of education. So it is necessary for the school to make the selection of candidates qualified teachers. Manual system used in selecting the teacher takes a very long and less efficient, because the sequence of manual selection very much. The purpose of this study is to design a decision support system that serves to make the selection of candidates qualified teachers to be educators in the school. System development method used is the method of weighting a value corresponding to a predetermined weight, while the design of the system used is DFD (Data Flow Diagram). The software used in the design of the system, among others, MySQL, PHP and XAMPP as a local server. This study resulted in a decision support system that allows the school in the process of teacher selection As well as decision support system makes a selection of more effective and efficient because the process is faster. Keywords: Systems, Supporting the decision, weighting, teachers, DFD, php, mysql.